A tactical periodisation model for Gaelic football. Issue 1 (February 2022) - Mangan, Shane; Collins, Kieran; Burns, Con; O'Neill, Cian
Tactical Periodisation is a training methodology, originally developed for soccer, that focuses primarily on the systems of play that a team intends to use in competition. It has been popularised by successful European coaches and subsequently has been proposed as a model to follow for other sports such as rugby union and tennis in more recent times. Gaelic football is an amateur sport that has similarities to soccer and rugby union. To date no training periodisation model has been proposed for Gaelic football. The aim of this article was to present a Tactical Periodisation model for Gaelic football, taking the sport's game structure, physical and technical demands and amateur status into account.